(untitled) (Web of Teachers: Inderscience Research, 2024)
In recent years some of the regions of Uzbekistan is facing big declines in sales. “In August 2024, the largest regional declines in real estate transactions were recorded in Syrdarya 22.6%, Khorezm 13.2%, and Tashkent city 9.7%” (kun.uz, 2024). However, despite nearly 10% of decline in Tashkent, there are 638 apartment buildings, which contains 28 thousand apartments were built in 2024 in only Tashkent city. (UzDaily.uz, 2024). So, is Uzbekistan investing on real estate more than demand?